Les ports d’Ifrīqiya et les stratégies des califes fatimides dans le Maghreb central - Dominique Valérian (Université de Provence, 2016)
Consolidating Aghlabid legacy with the Foundation of Mahdiya, the Fatimids relied on a port network which was already effective in the Central Mediterranean, and widely open toward the East, but slightly developed in their other western possessions in the Maghreb. The first objective of these ports was to control the siculo-ifrīqiyan space, in order to use it as a solid basis for their Eastern ambitions. Maghrebian military campaigns (against the Kharijits or in the West the Idrisids and small rulers, more or less linked to the Umayyads of Córdoba) remained for a long time purely terrestrial and followed the traditional routes used by Muslim armies since the conquest. The Umayyad attacks across the Straits of Gibraltar, their assumption of the Caliphate, but also the action of pirates threatening the navigation in the Central Mediterranean, decided or obliged the Fatimids to engage in a large struggle in the central and occidental Maghreb which, for the first time since the Muslim conquest, placed the ports and the littorals in the first place of strategic preoccupations. By expanding their action in the port cities of the whole Maghreb – and not only those of Ifrīqiya –, the Caliphs’ policy broke with that followed by the Muslim powers until then, and prepared the systematic development of the coastline by the rulers of the central Maghreb, Zirids and Hammadids, in the 11th century.